2013
DOI: 10.1086/673875
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Biology of Tail Autotomy in Lizards

Abstract: Self-amputation (autotomy) of the tail is essential for the survival of many lizards. Accordingly, it has garnered the attention of scientists for more than 200 years. Several factors can influence the release of the tail, such as the size, sex, and age of the lizard; type of predator; ecology; and evolutionary history of the lineage. Once lost, the tail will writhe for seconds to minutes, and these movements likely depend on the size and physiology of the tail, habitat of the lizard, and predation pressure. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 49 publications
0
45
0
Order By: Relevance
“…Although such studies have revealed notable relationships between morphology (tailed versus tail-less) and performance (sprint speed, jumping and stability), the biomechanical changes in locomotion associated with tail autotomy are less well understood (Higham et al, 2013;McElroy and Bergmann, 2013). Knowledge of how force production and limb joint mechanics during locomotion change with the loss of weight and shift in center of mass (CoM) associated with tail autotomy is crucial to link the radical change in morphology with measured performance (Downes and Shine, 2001;Chapple and Swain, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although such studies have revealed notable relationships between morphology (tailed versus tail-less) and performance (sprint speed, jumping and stability), the biomechanical changes in locomotion associated with tail autotomy are less well understood (Higham et al, 2013;McElroy and Bergmann, 2013). Knowledge of how force production and limb joint mechanics during locomotion change with the loss of weight and shift in center of mass (CoM) associated with tail autotomy is crucial to link the radical change in morphology with measured performance (Downes and Shine, 2001;Chapple and Swain, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As more studies begin to measure ground reaction forces and detailed kinematics of running lizards before and after tail loss, we will be better positioned to develop predictive frameworks for understanding how autotomy influences locomotor behavior and performance. Until then, we can rely on a wide range of studies from the past 50 years as well as several recent and thorough reviews Higham et al, 2013b;McElroy and Bergmann, 2013) to seek patterns to help us understand the impacts of tail loss on different locomotor modes, as discussed below.…”
Section: Ground Reaction Forcementioning
confidence: 99%
“…Tail autotomy plays an essential role in survival of various lizards [22]. They initiate autotomy when seized or poisoned by a predator during predator-prey interactions [3].…”
Section: Evolutionary Aspects Of Autotomy and Regenerationmentioning
confidence: 99%
“…Furthermore, fat layer in tail may facilitate autotomy [1] in autotomous lizards, because of the presence of perivertebral adipose tissue deep in muscles and adjacent to the vertebrae unlike nonautonomous lizards [31]. Additional factors can contribute in the release of tails during predator attack including type of predators; age, size and sex [46] of the lizards; ecology and evolution of their ancestral lineage [22]. Evolution of caudal muscle, however, has been found to reduce the ability of caudal autotomy in some other lizards [47].…”
Section: Factors Affecting the Tail Autotomy And Regenerationmentioning
confidence: 99%